PENGARUH KUALITAS PELAYANAN DAN PERSEPSI KONSUMEN TERHADAP KEPUASAN KONSUMEN DALAM MENGGUNAKAN JASA DI RSUD IBNU SINA KABUPATEN GRESIK - Khadijah, S.E., M.M., Susan Novitasari; Dianasari, Ika Ayu (GEMA EKONOMI, 2018)
This study aims to examine and prove the influence of service qualityand consumer perceptions on customer satisfaction in using services atthe General Hospital of Ibnu Sina Region of Gresik Regency. Thisresearch uses quantitative approach with multiple linear regressionanalysis. The population in this study were patients and families ofpatients who visited the General Hospital of Ibnu Sina District Gresik,which amounted to 16,244 people in October of 2017. To determine thenumber of samples using the formula slovin so that the sample obtainedby 99 respondents and data collection is done with distribution ofquestionnaires. The results of this study indicate that the quality ofservice has a major and significant impact on customer satisfaction inusing services at the General Hospital of Ibnu Sina Region of GresikRegency. While consumer perception have a positive and significantinfluence on customer satisfaction in using services at the GeneralHospital of Ibnu Sina Region of Gresik Regency. This means that thequality of service and consumer perception simultaneously affect thesatisfaction of consumers in using services at the General Hospital ofIbnu Sina Region of Gresik Regency. DOI : 10.5281/zenodo.3475676